Product market regulation and productivity convergence - Conway, Paul (OECD Publishing, 2007)
Product market regulation in the OECD area has generally become less restrictive of competition over recent years. This has lead to a degree of convergence in regulatory policies, but nonetheless, the productivity performance of OECD countries has become increasingly disparate. Indeed, according to some measures, the growth rates and levels of labour productivity have recently begun to diverge. Recent developments in the theory and empirics of growth suggest that cross-country productivity patterns may partly reflect differences in the policy and institutional environment (Acemoglu et al., 2004; Aghion and Griffith, 2005; Nicoletti and Scarpetta, 2003)
Keywords: Economics